Predicting citizens acceptance of government-led e-participation initiatives through social Media: a theoretical model - Alarabiat, Ayman (2017)
Whilst the idea of utilizing social media to advance government-led e-Participation initiatives has proliferated significantly in recent years, mostly such initiatives do not meet the intended expectations, as the majority of them fail to attract wider citizens’ audience. Overall, the key factors that could explain and predict citizens’ participation are not yet thoroughly identified. Therefore, the current study develops a theoretical citizen-centric model that seeks to explain and predict the intention of citizens’ behavior towards their involvement in government-led e-Participation initiatives through social media. The methodological approach is primarily based on utilizing and extending one of the well-known theories for describing a person acceptance behavior, namely the Theory of Planned Behavior. The model applies the main constructs of the Theory – attitude, subjective norms, and perceived behavioral control; and complements them with several constructs drawn from relevant literature. The paper contributes to understanding the reasons why citizens decide to engage or not in government-led e-Participation initiatives through social media.